Development of Scramble Media for Arabic Language Learning to Improve Listening Skills of Grade 5 Students at MIN Banda Aceh - Mukhlisah, Mukhlisah; Rahmayani, Hafiza; Hidayatullah, Wahyu (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2026)
This study aims to develop scramble media for Arabic language learning to improve students' listening skills and train them to improve their concentration and thinking speed in grade 5 at MIN Banda Aceh. The research method used is the R&D (Research and Development) method, with the ADDIE model consisting of five stages: analysis, design, development, implementation, and evaluation. The results of this study are, first, presenting vocabulary in the form of animated videos combined with scrambled media to improve students' listening skills in Arabic language learning. Second, students enjoy using scrambled media and can practice their listening skills, thereby increasing their concentration and thinking speed.